Comparative collocation(al) analysis between two Malaysian online newspapers: a case study of the 2020 Sabah election day - Siti Aeisha Joharry,; Syamimi Turiman,; Maizura Mohd Noor, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The cases of COVID-19 in Malaysia recorded a significant spike after the Sabah State Election, which was held on 26 September 2020. This paper aims to examine news reporting strategies before, during, and after the Sabah Election Day in Malaysia. Related articles from two online local newspapers (one mainstream and one alternative) are compiled into a corpus for this purpose and compared against each other. Using the corpus-assisted discourse approach, #LancsBox6.0 was used to compare statistically significant keywords and their collocates to analyse differences in the way the election was portrayed in both media channels. Findings revealed that both newspapers described news in relation to the number of COVID-19 cases in proximity to reporting of the state election. Arguably, reporting of events is (slightly) different and therefore has repercussions on the way news is represented in mainstream and alternative media. For example, although both online sources reported the significance of the Sabah state election to the rise in COVID-19 cases in Malaysia, The Star used more explicit referencing (e.g., is from Sabah; cases in Sabah) and had a more speculative type of reporting as some of the collocations were found to be from politicians’ verbatim that indicated their weak arguments while Malaysiakini provided reports that proved the elections to have had a spill-over effect on the total number of COVID-19 cases in Malaysia. Collocation networks also proved to show differences in the way words are used in language and discourse and can be further explored in future studies.